1993
DOI: 10.1111/j.1365-2265.1993.tb01007.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in patients with hyperthyroidism measured by dual energy X‐ray absorptiometry

Abstract: These findings suggest that bone mineral density is decreased in patients with hyperthyroidism and that TSH receptor antibody, osteocalcin, and alkaline phosphatase are sensitive markers of bone metabolism alterations in hyperthyroidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
33
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 18 publications
6
33
2
Order By: Relevance
“…Our data suggest that the effect of restoration of the euthyroid state is greater than the potential benefits of CT at the doses employed. This agrees with the lack of influence of the menopause in the BMD from patients with active hyperthyroidism (8). So, hyperthyroidism exerts a profound alteration in bone dynamics and surpasses the effects of sex, menopause, and antiresorptive treatment with CT at the doses used in this study.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Our data suggest that the effect of restoration of the euthyroid state is greater than the potential benefits of CT at the doses employed. This agrees with the lack of influence of the menopause in the BMD from patients with active hyperthyroidism (8). So, hyperthyroidism exerts a profound alteration in bone dynamics and surpasses the effects of sex, menopause, and antiresorptive treatment with CT at the doses used in this study.…”
Section: Discussionsupporting
confidence: 75%
“…In histomorphometric studies, reconstruction of the remodeling sequence in patients with hyperthyroidism discloses a marked shortening of both the resorptive and formative phases of the remodeling cycle, with a negative balance of 9 -10 m/remodeling cycle (3). Osteoclastic and osteoblastic activities are enhanced, with a predominance of bone resorption resulting in increased levels of bone turnover markers (4) and in decreased bone mass, as determined by single photon absorptiometry (5), dual photon absorptiometry (6), and dual x-ray absorptiometry (7,8), which is the most rapid, accurate, and reproducible method to evaluate bone mineral density (BMD) (9, 10).Serum bone alkaline phosphatase determined by immunoradiometric assay (IRMA) and serum type I collagen Cterminal telopeptide (ICTP) determined by RIA have been introduced recently as formation and resorption bone turnover markers, respectively (11). These precise bone markers could clarify, in a prospective study, the existence of a bone mass recovery period after attainment of euthyroidism that has been suggested in patients treated with radioiodine (12).…”
mentioning
confidence: 99%
“…Hyperthyroidism causes reduction in bone mineral density (BMD) assessed by the measurement of lumbar vertebrae and femur by dual energy X-ray absorptiometry (DEXA) [271]. Hyperthyroidism affects bone mineralization especially during the early post-menopausal period and the effect is mainly at the cortical bone [272].…”
Section: Discussionmentioning
confidence: 99%
“…But the group with a distal bone fracture had a remarkably and statistically higher number of C cells (P<0.01) at the time of bone fracture than the groups with fractures at other sites. In the case of fracture of the lateral proximal s esamoid, changes in the blood concentrations of parathyroid gland hormone and calcitonin were found to differ, suggesting that calcitonin adjustment was different at the time of fracture of a large bone and the lateral proximal sesamoid [1,8]. In the present study, comparison of the number of previous races with the number of C cells in 131 racehorses revealed that 2-year, 3-year and 4-year-old racehorses had a tendency for an increase in the number of C cells with an increase in the frequency of races.…”
Section: Discussionmentioning
confidence: 99%